Graduate Tracer Study III: A report of a survey of graduates from ECIAF - National Institute of Higher Education, Research, Science and Technology (NIHERST, 1989)
This study which is part of an exercise assessing all national agriculture graduates, addressed persons who graduated from the Eastern Caribbean Institute of Agriculture and Forestry (ECIAF) between 1966-1986. The survey frame covered 618 graduates—525 trained in agriculture and 149 in forestry. It was found that in the preceding 20 years, ECIAF graduated 674 nationals, the majority of whom were male. Almost one quarter of them sought higher-level qualification approximately 5 ½ years after having obtained their diploma. After having waited just under one year before gaining employment, the large majority was absorbed into the government sector in general agriculture, education, and research activities.
Keywords: graduates; ECIAF